Global Financial Stability Report, April 2013 : Old Risks, New Challenges. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2013)
The Global Financial Stability Report examines current risks facing the global financial system and policy actions that may mitigate these. It analyzes the key challenges facing financial and nonfinancial firms as they continue to repair their balance sheets. Chapter 2 takes a closer look at whether sovereign credit default swaps markets are good indicators of sovereign credit risk. Chapter 3 examines unconventional monetary policy in some depth, including the policies pursued by the Federal Reserve, the Bank of England, the Bank of Japan, the European Central Bank, and the U.S. Federal Reserve.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet